Contextual cueing in older adults: Slow initial learning but flexible use of distractor configurations. Issue 5 (14th September 2019) - Preuschhof, Claudia; Sharifian, Fariba; Rosenblum, Lisa; Pohl, Tanja Maria; Pollmann, Stefan
ABSTRACT: Learned spatial regularities can efficiently guide visual search. This effect has been extensively studied using the contextual cueing paradigm. We investigated age-related changes in the initial learning of contextual configurations and the relearning after target relocation. Younger and older participants completed a contextual cueing experiment on two days. On day one, they were tested with a standard contextual cueing task. On day two, for the repeated displays the location of the targets was moved while keeping the distractor configurations unchanged. Older participants developed a reliable contextual cueing effect but the emergence of this effect required more repetitions compared to younger individuals. Contextual cueing was apparent quickly after target relocation in younger and older participants. Especially in older adults, the fast updating might be due to learned distractor-distractor associations rather than the updating of target-distractor configurations.